2021
DOI: 10.3390/ijerph18042192
|View full text |Cite
|
Sign up to set email alerts
|

Gender Patterns in Mobbing Victims: Differences in Negative Act Perceptions, MMPI Personality Profile, Perceived Quality of Life, and Suicide Risk

Abstract: With the aim of investigating the impact of gender-related personality characteristics on bullying perceptions and outcomes, a correlational study was designed with 114 individuals who had used a public health service aimed at harassed workers identifying themselves as victims of mobbing in central Italy. The study was conducted using the following questionnaires: the Negative Acts Questionnaire (NAQ), a measure of workplace bullying; the Minnesota Multiphasic Personality Inventory (MMPI-2), used to provide in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 82 publications
(150 reference statements)
0
5
0
Order By: Relevance
“…Mobbing is a complex phenomenon with a number of facets, which merits further academic attention (Einarsen, Hoel, Zapf & Cooper, 2011;Nielsen, Indregard & Øverland, 2016) but, in any event, there are several studies that focus on the organizational perspective, with less importance placed on the possible link between harassment perceptions and a victim's personal characteristics (Mikkelsen & Einarsen, 2002;Einarsen & Nielsen, 2015). In light of this, it seems crucial to understand the various factors playing a role in the association between workplace bullying perceptions and outcomes, such as having certain personal characteristics and dispositions (Djurkovic, McCormack & Casimir, 2006;Glasø, Vie, Holmfjord & Einarsen, 2011;Alfano, Ramaci, Landolfi, Presti & Barattucci, 2021).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Mobbing is a complex phenomenon with a number of facets, which merits further academic attention (Einarsen, Hoel, Zapf & Cooper, 2011;Nielsen, Indregard & Øverland, 2016) but, in any event, there are several studies that focus on the organizational perspective, with less importance placed on the possible link between harassment perceptions and a victim's personal characteristics (Mikkelsen & Einarsen, 2002;Einarsen & Nielsen, 2015). In light of this, it seems crucial to understand the various factors playing a role in the association between workplace bullying perceptions and outcomes, such as having certain personal characteristics and dispositions (Djurkovic, McCormack & Casimir, 2006;Glasø, Vie, Holmfjord & Einarsen, 2011;Alfano, Ramaci, Landolfi, Presti & Barattucci, 2021).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Many studies investigating the reasons for the emergence of mobbing in business life reveal that this may be due to organizational structure, social groups or individual reasons (Zapf, 1999;Hogh et al, 2011;Shallcross et al, 2013;Lutgen-Sandvik et al, 2009). Accordingly, one of the reasons that are discussed as whether it causes mobbing and is considered as the possibility of triggering mobbing or being exposed more is the gender factor (Goralewska-Slonska, 2019;Erdis et al, 2021;Kavocic et al, 2017;Çöğenli et al, 2017;Alfano et al, 2021). When the relevant literature is reviewed, some studies have concluded that İş Yaşamında Cinsiyet Temelinde Mobbing Algısı Üzerine Bir Meta Analiz Çalışması…”
Section: Demi̇rel İş Yaşamında Cinsiyet Temelinde Mobbing Algısı üZe...mentioning
confidence: 99%
“…Many dysfunctional aspects of organizations and their corresponding degeneration are discussed extensively in the research already conducted on this phenomenon [7]. However, the issue of WPB appears to be more complex and difficult to address, as it is associated not only with organizational determinants but also with personal variables [8]. WPB results from a relationship between organizational factors (e.g., climate), work attitudes, and health [9].…”
Section: Introductionmentioning
confidence: 99%